Diplomasi Teknologi Indonesia dan Spanyol dalam Pengembangan Pesawat Baling-Baling - Almira Dewi Zaskya (Universitas Airlangga, 2019)
This research analyzes technological diplomacy in Indonesia and Spainrelations, especially in the field of the aerospace industry technology(propeller aircraft development) that is conducted by PT DirgantaraIndonesia and Airbus Military Spain. This research will explain thedevelopment process of aerospace industry and technology since 1975.Qualitative descriptive methodologies used in this research to obtainin-depth analysis. The result of the analysis shows that there is a closerelationship beyond just the institutional relationship, that is therelationship between the two countries in this technology diplomacy.From this study it can be concluded that the technology diplomacy thathas been running and manifestly implemented for over 40 years has getto both countries having a very close and profitable relationship. Therelationships and cooperation that can be said to be familial is believed byboth parties will continue into the future.